ANALISIS PENGGUNAAN CAMPUR KODE DALAM CERAMAH K.H. BAHAUDDIN NUR SALIM - Ali Manshur; Dewi Fatimatuz Zahro (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
This research is a study of the use of code mixing in K.H's lectures. Bahauddin Nursalim downloaded on YouTube. The background of this research is the lecture has an important role in presenting oral explanations to the audience both for the present or the future. Communities will easily accept ideas from those who are adept at speaking in a variety of ways by lecturers. The purpose of this research is to describe the form of code mixing, types of code mixing, and factors for the occurrence of language code mixing in K.H’s lectures. Bahauddin Nursalim. This type of research is qualitative. The subject of this research is the speech K.H. Bahauddin Nursalim, while the object of research is mixed language code used by K.H. Bahauddin Nursalim in the lecture. Data obtained by downloading videos from YouTube channel Serambi Narukan as many as five episodes. Data collection was carried out by listening methods followed by tapping techniques, competent free involve listening techniques and note taking techniques. The method of data analysis was carried out interactively including, (1) Data reduction, at this stage the researcher listened to K.H's lecture. Bahauddin Nursalim which has been downloaded from YouTube to collect data mixed language codes. (2) Presentation of data, i.e. in this study the data is presented in tabular form so that it is easy to understand, then the data is narrated. (3) Withdrawal of Conclusions, i.e. the data are inferred based on the research objectives in a descriptive form. The results showed that (1) The form of code mixing in K.H's lectures. Bahauddin Nursalim in the form of words, phrases and clauses. (2) the type of code mix used in K.H's lecture. bahauddin Nursalim in the form of mixed code in, mixed code out, and mixed code mixed. (3) Factors of code mixing in K.H.'s lecture Bahauddin Nursalim includes speakers and speech partners in relaxed situations, speakers to show their intelligence, and the need for foreign language expressions because there is no appropriate language equivalent in use